"Rwanda cannot be exorcised" : representations of the trauma of the Rwandan Genocide in selected films and novels - Jennings, Kathleen (Rhodes University, Faculty of Humanities, Department of Literary Studies in English)
Although the Rwandan genocide (itsembabwoko in Kinyarwanda) has often been compared with the Holocaust, in terms of literary and cinematic narratives it has been largely underrepresented, with the notable exception of the release of the films Hotel Rwanda (2004) and Sometimes in April (2005), as well as novels such as Gil Courtemanche's A Sunday at the Pool in Kigali (2003). However, although there is now a larger oeuvre of works on the subject, they are often not widely known or disseminated beyond their countries of origin. Of even greater concern is the fact that most cinematic narratives on itsembabwoko rely on Western narrative structures in their approach to storytelling. As a result, trauma in these narratives largely tends to focus on the experiences of Western protagonists or on Rwandan protagonists from a Western point of view. This tendency can be tied to the use of Western trauma theory in exploring the effects of the genocide on its witnesses and survivors, at the expense of arguably more relevant postcolonial trauma theory. This presents a problem in theorising the trauma of itsembabwoko, which occurred in a highly specific historical context involving the processes of colonization and decolonization, and in which the difficulties in unifying a population which had been split along socio-economic lines since pre-colonial times remained unresolved. Despite its shortcomings in the postcolonial African context, it would be a mistake to dismiss Yale trauma theory entirely, however, since theorists such as Cathy Caruth still provide valuable insights into the effects of trauma on both the individual and the collective. As a result, I have sought to find commonalities between the two schools of thought, so as to create a more nuanced view of itsembabwoko, its repercussions and the violence preceding it. In writing this thesis, I have selected mostly Rwandan authors, often survivors of the genocide, whose works provide an alternative view of Rwanda's violent history to that presented in the works mentioned above. Given that the majority of the texts I focus on have been released more recently "“ mostly the mid-2010s "“ and are less well-known than their Western counterparts, they provide the opportunity to compare first-hand accounts with those that can only partially recreate the terror of anti-Tutsi violence in Rwanda. My analysis hopefully provides a new perspective on the dominant narratives which have shaped the way in which non-Rwandan (predominantly Western) audiences understand the genocide. The overall aim of this thesis, then, is to demonstrate the importance of placing the genocide and its resultant trauma in a broader historical context, with a view to establishing that it is shortsighted to ignore the impact of pre- and post-genocide trauma on the Rwandan people when discussing itsembabwoko. Though this has been achieved in socio-historical studies, such as Mahmood Mamdani's When Victims Become Killers: Colonialism, Nativism, and the Genocide in Rwanda, very little has been produced on literary and cinematic representations of the genocide.
Keywords: Rwandan Genocide, Rwanda, 1994; Genocide in literature; Genocide in motion pictures; Psychic trauma; Postcolonialism; Collective memory Rwanda